2018
DOI: 10.1186/s40643-018-0199-3
|View full text |Cite
|
Sign up to set email alerts
|

Green microalgae biomolecule separations and recovery

Abstract: Microalgae biomass has garnered significant attention as a renewable energy feedstock and alternative to petroleumbased fuels. The diverse metabolism of green microalgae species additionally provides opportunities for recovery of products for feed, food, nutraceutical, cosmetic, and biopharmaceutical industries. Recently, the concept of using microalgae as part of a biorefinery model has been adopted in place of refinery methods focused on recovering one target product. This has led to producers exploring co-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(59 citation statements)
references
References 167 publications
0
59
0
Order By: Relevance
“…Carotenoids such as astaxanthin, β-carotene, and lutein can be included as part of topical cosmetic products for protection against UV-induced damage [18,20,24]. Specifically, β-carotene is used in the formulation of skin care products [21,41].…”
Section: Algae In Skincare With Special Attention To Sunscreen and Anmentioning
confidence: 99%
See 2 more Smart Citations
“…Carotenoids such as astaxanthin, β-carotene, and lutein can be included as part of topical cosmetic products for protection against UV-induced damage [18,20,24]. Specifically, β-carotene is used in the formulation of skin care products [21,41].…”
Section: Algae In Skincare With Special Attention To Sunscreen and Anmentioning
confidence: 99%
“…Among them, astaxanthin also presents interesting depigmentation properties which provide a protection for skin from age spots by reducing melanin production by 40% and improving all skin layers [191][192][193]. Therefore, astaxanthin, can be included as part of topical cosmetic products for protection against hyper-pigmentation, and the same is valid for β-carotene and lutein [18,20,24,193]. Fucoxanthin can also help to reduce the activity of tyrosinase and melanogenesis [193,194].…”
Section: Algae and Their Compounds In Skin Whiteningmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reported in the literature demonstrated that the most critical steps to recover internally stored biomolecules are cell disruption and fractionation of bioderived products by a clean technology …”
Section: Introductionmentioning
confidence: 99%
“…However, within a ‘circular economy’ strategy, the valorization of the main high added‐value compounds by the use of green solvents and green technologies is sought. The general consensus is that the high value of different final products has the potential to increase the total value of microalgae biomass . For these reasons, the aim of this work is to study an alternative approach to valorize the main constituents of the microalgal biomass, fractionating hydrophobic from hydrophilic compounds with a tuned sustainable biorefinery strategy.…”
Section: Introductionmentioning
confidence: 99%